2007
DOI: 10.1002/bdd.537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macrolide antibiotics on uptake of digoxin into rat liver

Abstract: The objective of this study was to examine the effect of macrolide antibiotics, clarithromycin, erythromycin, roxithromycin, josamycin and azithromycin, on the hepatic uptake of digoxin. The uptake of [(3)H]digoxin was studied in rats in vivo, using the tissue-sampling single-injection technique, and in isolated rat hepatocytes in vitro. The uptake of [(3)H]digoxin into rat hepatocytes was concentration-dependent with a Michaelis constant (K(m)) of 445 nM. All the macrolide antibiotics inhibited the uptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Because digoxin is an Oatp1a4-specific substrate (Shitara et al, 2002), our result implies that the transport function of Oatp1a4 was greatly reduced during the 96-h culture period required for SCH. In our data, half of the digoxin uptake was dominated by active saturable transport in isolated rat hepatocytes, whereas a previous report indicated that 79% of its uptake was saturable in cultured rat hepatocytes (Ito et al, 2007). The apparent discrepancy may come from the different experimental systems and possible alteration of passive permeability through the inhibition of Na ϩ /K ϩ -ATPase by 100 M digoxin.…”
Section: Uptake Activity In Sandwich-cultured Hepatocytescontrasting
confidence: 91%
“…Because digoxin is an Oatp1a4-specific substrate (Shitara et al, 2002), our result implies that the transport function of Oatp1a4 was greatly reduced during the 96-h culture period required for SCH. In our data, half of the digoxin uptake was dominated by active saturable transport in isolated rat hepatocytes, whereas a previous report indicated that 79% of its uptake was saturable in cultured rat hepatocytes (Ito et al, 2007). The apparent discrepancy may come from the different experimental systems and possible alteration of passive permeability through the inhibition of Na ϩ /K ϩ -ATPase by 100 M digoxin.…”
Section: Uptake Activity In Sandwich-cultured Hepatocytescontrasting
confidence: 91%
“…Measurement of the levels of these enzymes is considered as an indication of the severity of the damage to the liver, as evidenced, for example, by the presence of higher levels of the AST cytoplasmic isoenzyme than those of the mitochondrial isoenzyme. Levels of this enzyme are increased during acute liver diseases (12) and during severe damages in the cells of the kidneys, pancreas, and red blood cells, while levels of ALT and AST increase in association with liver necrosis (9). Table 1.…”
Section: Resultsmentioning
confidence: 99%